A177 METHOTREXATE FOR THE INDUCTION OF REMISSION IN ULCERATIVE COLITIS. (4th March 2021) - Hudson, D; Lakhani, R; MacDonald, J; Chande, N; McDonald, J W
Abstract: Background: Obtaining steroid-free remission in Ulcerative Colitis (UC) is a clinically important parameter that can mitigate the development of disease-related complications and lead to improved quality of life. Aims: A systematic review to assess the effects and safety of methotrexate for induction in patients with UC. Methods: MEDLINE, EMBASE, CENTRAL were searched from inception to August 20, 2020. Randomized controlled trials (RCTs) comparing methotrexate with placebo or an active comparator in patients with active ulcerative colitis were considered for inclusion. The primary outcome measure was the proportion of patients who achieved clinical remission and withdrawal from steroids as defined by the studies and expressed as a percentage of the total number of patients randomized (intention-to-treat analysis). The overall quality of the evidence supporting the primary outcome was assessed using the GRADE criteria. Results: Three studies (n=212) were included in the review. Two studies were randomized controlled trials comparing methotrexate to placebo for induction of remission of active ulcerative colitis. The first study (n = 67) compared oral methotrexate (12.5 mg/week) to placebo. Forty-seven percent (14/30) of methotrexate patients achieved clinical remission and complete withdrawal from steroids during the study period compared to 49% (18/37) of placebo patients (RR 0.96, 95% CI 0.58 to 1.59). A GRADE analysis indicated that the overall quality of the evidence supporting this outcome was low due to very sparse data. The second study (n=111) compared subcutaneous/intramuscular methotrexate 25 mg/week to placebo. The primary outcome, steroid-free remission at week 16, was present in 32% (19/60) of patients on methotrexate in comparison to 20%(10/51) of patients in the placebo arm (RR 1.62; 95% CI 0.83 to 3.15; P-value of 0.15). A GRADE analysis indicated downgrading of the evidence to low given very sparse data (29 events). An additional head-to-head randomised controlled study (n = 34) compared oral methotrexate (15 mg/week) to 6-mercaptopurine (1.5 mg/kg/day) and 5-aminosalicylic acid (3 g/day). This final study was judged to be at high risk of bias due to an open-label design. At 30 weeks, 58% (7/12) of methotrexate patients achieved clinical remission and withdrawal from steroids compared to 79% (11/14) of 6-mercaptopurine patients (RR 0.74, 95% CI 0.43 to 1.29) and 25% (2/8) of 5-aminosalicylic acid patients (RR 2.33, 95% CI 0.64 to 8.49). GRADE analyses indicated that the overall quality of the evidence was very low due to very sparse data and high risk of bias. Conclusions: Methotrexate demonstrated no benefit over placebo or active comparators for the induction of steroid-free remission. Future research is ongoing to explore the utility of combination therapy with monoclonal antibody biologic therapy for the treatment of active ulcerative colitis. Funding Agencies: None